EVALUATION OF PHYTOTOXICITY AND ANTIFUNGAL ACTIVITY AGAINSTColletotrichum acutatum OF ESSENTIAL OILS OF THYME (Thymus vulgaris), LEMONGRASS (Cymbopogon citratus), AND ITS MAIN CONSTITUENTS - ALZATE O., Diego A.; MIER M., Gonzalo I.; AFANADOR K., Lucia; DURANGO R., Diego L.; GARCÍA P., Carlos M. (Vitae, 2009)
Anthracnose of tree tomato, caused by the fungus Colletotrichum acutatum, is the major postharvest disease of this crop in Colombia due to its widespread distribution and economic loss. In the present work, antifungal activity against C. acutatum specie with the essential oils (EO) of thyme (Thymus vulgaris), lemon grass (Cymbopogon citratus), and the main components of the EO, thymol and citral, is evaluated. Experimental result indicates that thymol at a concentration of 125 mg/L and citral at 300 mg/L, inhibits completely the mycelial growth during eleven days. Spore germination is affected 100% with lemon grass oil at 350 and 400 mg/L, thymol at 100 and 125 mg/L, and citral at 250 and 300 mg/L, during the period of evaluation of twelve hours. In addition, thymol at 125 mg/L and citral at 300 mg/L, inhibits completely the sporulation of the fungus whereas thyme oil at 350 mg/L shows a lower degree of affectation. Phytotoxicity evaluations of all materials by applying drops located at the leaf surface of Solanum betacea to concentrations between 150 and 5000 mg/L, demonstrate that treatments do not induce any apparent damage. Also, foliar spraying complete and systematically every 2 days, for the period of 2 months with constant concentration of 1500 mg/L for each evaluated materials, produces no sign of wilting, deteriorating growth or alteration of the overall development of the plants.